ALAT-ALAT KOHESI DALAM NOVEL INSURGENT KARYA VERONICA ROTH - ROEROE, MENTARY M. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2017)
ABSTRACT  The research is entitled ?The  Cohesion Items of the Novel Insurgent by Veronica Roth?.    The research questions are what is cohesion items appear  in the novel Insurgent This research aims at to identify, clasification, analyze and describe  the cohesion  items used  in the novel Insurgent The theory used is Halliday and Hasan (1976) that describe text connectedness in terms of reference, substitution, ellipsis, and conjunction. Cohesion occurs ?when the interpretation of some element in the discourse is dependent on that of another? (Halliday and Hasan, 1976:4). The  types of cohesion are distinguished 1)References, 2) Substitution, 3)Ellipsis, dan 4) Conjunction. The method used in this research is descriptive method. Descriptive method is a method used to describe or analyze the results of the study but not used to make broader conclusions (Sugiyono 2005: 21). This method of describing what it is about cohesion instruments that have been classified  and put them on cards. Research results show that cohesion tools that used by the writer are: 1) reference with types of  a) personal reference (noun/pronoun and possessive), demonstrative and comparative. Personal reference are; I, me, mine, my all infact refer to the character of Tris. Other personal reference, you, your, we us, our, he, him, his, she, her, they, them refer to other character in this novel, the character of Tobias, Johanna, Marcus, Tris, Tris Friends, the boy at the left side of Tris, Jack, Lynn, Fernando, Peter, Eric, Caleb, Hector and Christina. b) Demonstrative reference, like the use of this, these, here refer to near distance and that, those, there, then refer to far distance, c)  Comparative reference, like better, more are adjectives, so and more are adverbs. 2) Susbtitution, like one is nominal category, do is verbal categore, so not are clausal. 3) Elliptical, subject deleting. 4) Conjunction, like additive form, alternative, adversative, containing, clausal, temporal, and simultanouse (consultive, correlative form)  --------------------------------------------------- Keywords: cohesion, reference, substitution, ellipsis, conjuction